2015
DOI: 10.1002/ajmg.a.37068
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative associations of scalp and body subcutaneous neurofibromas with internal plexiform tumors in neurofibromatosis 1

Abstract: Internal plexiform neurofibromas are a major cause of adverse outcomes in patients with neurofibromatosis 1 (NF1). We investigated the relationship of the numbers of subcutaneous neurofibromas of the scalp or body to internal plexiform tumor volume in 120 NF1 patients who had undergone whole body magnetic resonance imaging (MRI). We identified internal plexiform neurofibromas in 55% of patients, subcutaneous neurofibromas of the body in 75%, and subcutaneous neurofibromas of the scalp in 45%. The number of sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Forty papers (74.1%) were exclusively about children and adolescents, and in 13 papers (24.1%) the focus was on both children/ adolescents and adults, but the majority of patients were still younger than 19 years old. The majority of participants were adults in only one of the included papers [42].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Forty papers (74.1%) were exclusively about children and adolescents, and in 13 papers (24.1%) the focus was on both children/ adolescents and adults, but the majority of patients were still younger than 19 years old. The majority of participants were adults in only one of the included papers [42].…”
Section: Resultsmentioning
confidence: 99%
“…We found that the term "whole-body MRI" is used interchangeably for examinations covering from two-thirds to the whole body. For instance, whole-body MRI performed for staging of malignant disease sometimes covers skull-base to mid-thigh only [42,52,54,[67][68][69], similar to what is often being used for PET-CT. According to some authors, important additional clinical information, like therapy-related osteonecrosis of the knees/ankles [55] or distant metastases in the extremities [73] could be missed due to this limited FOV, hence a clear definition of what should be covered in the scan must be defined when recommending whole-body MRI for specific diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a large whole-body tumor volume is associated with an increased tumor growth [5]. Proposed risk factors for a large whole-body tumor volume are female gender and high numbers of subcutaneous Neurofibromas [6,7]. PNF can undergo transformation into malignant peripheral nerve sheath tumors (MPNST) in 8-13% of NF1 patients [8].…”
Section: Introductionmentioning
confidence: 99%
“…There are three subtypes of neurofibroma based on their location and appearance: (i) localized cutaneous or dermal neurofibromas, which are the most common, appear at puberty and grow from small nerves in the skin or just under the skin. They have limited growth, remaining benign throughout life, and do not transform into malignant PNSTs 5 ; (ii) diffuse or subcutaneous neurofibromas are typically located within the subcutaneous tissues of the head and neck, are often pigmented or with melanocytic differentiation 25, 28 , and in NF1 are associated with internal neurofibroma tumor burden and mortality 29, 30 ; and (iii) plexiform neurofibromas (PNF) are usually congenital, occurring in about a third of NF1 patients, and present anywhere in the body but often internal where they can remain aysmptomatic 26 . They involve multiple nerve fascicle trunks and infiltrate surrounding tissue 25 .…”
Section: Peripheral Nerve Sheath Tumors (Pnst) and Perineural Invamentioning
confidence: 99%